Disintegration of magnetic tablets in human stomach evaluated by alternate current Biosusceptometry - Corá, Luciana A. [UNESP] (2003)
Oral administration is the most convenient route for drug therapy. The knowledge of the gastrointestinal transit and specific site for drug delivery is a prerequisite for development of dosage forms. The aim of this work was to demonstrate that is possible to monitor the disintegration process of film-coated magnetic tablets by multi-sensor alternate current Biosusceptometry (ACB) in vivo and in vitro. This method is based on the recording of signals produced by the magnetic tablet using a seven sensors array and signal-processing techniques. The disintegration was confirmed by signals analysis in healthy human volunteers' measurements and in vitro experiments. Results showed that ACB is efficient to characterize the disintegration of dosage forms in the stomach, being a research tool for the development of new pharmaceutical dosage forms. © 2003 Elsevier B.V. All rights reserved.